Financing Information and Communication Infrastructure Needs in the Developing World : Public and Private Roles. - World Bank (Washington : World Bank Publications, 2005)
Over the past ten years, private-sector-led growth has revolutionized access to telecommunications. Every region of the developing world benefitted in terms of investment and rollout. This revolution would have been impossible without government reform and oversight. Advanced information and communication infrastructure (ICI) are increasingly important to doing business in a globalizing world. Governments, enterprises, civil society, workers, and poor populations in the developing countries need more affordable access. This report proposes strategies that governments can carry out to attract private investment and ensure the continued evolution and spread of information and communication infrastructure. These strategies encompass more than sector policy alone, for investment decisions are based on a wide range of factors including, for example, the roles played by financial sector development and the broader investment environment. The strategies also include potential public sector investments that can catalyze ICI rollout in subsectors where the private sector is not prepared to intervene on its own.
4. Investment and Expenditure in Telecommunications and ICT -- 5. Total (1990-2002) Telecommunications PPI per Region: -- 6. Prices and Competition -- 7. Impact of Private Investment on Rollout -- 8. Impact of Private Involvement on Rollout, Efficiency, and Investment -- 9. Data Competition, Prices, and Usage -- 10. Telecommunications Investment Requirements -- 11. Restrictions on Foreign Ownership of Telecommunications Service Operators -- LIST OF BOXES -- 1. IFC Activities in Support of Local Financing for Private Telecommunications -- 2. Somalia's Telecommunications Sector -- 3. The Determinants of Private Participation Levels in PPI Investments -- 4. Working Towards the Establishment of an ECOWAS Common Telecommunication Market -- 5. Accelerating Connectivity in Eastern & Southern Africa -- 6. Public Financing in Conflict and Post-Conflict Environments -- 7. Technology Neutrality in Investments Commitments -- 8. Andhra Pradesh Rolls Out Broadband -- 9. The Role of IFIs in Financing Private Telecommunications -- 10. IFC Investments in Telecommunications -- 11. A MIGA Guarantee -- 12. A World Bank Technical Assistance Loan -- 13. The Output-Based Aid Approach to Universal Access Funds Disbursements in Uganda -- 14. Policy Lending in Telecommunications -- 15. World Bank-Administered Trust Funds at Work -- 16. A New Global Instrument for ICI Rollout?.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2017. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Telecommunication -- Deregulation -- Developing countries; Telecommunication -- Developing countries; Telecommunication -- Privatization -- Developing countries